1984
DOI: 10.1017/s0033291700015099
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Eye Movement (REM) sleep: cholinergic mechanisms

Abstract: EDITORIALRapid Eye Movement (REM) sleep: cholinergic mechanisms 1 Otto Loewe conceived of the experiment that led to the discovery of Vagusstoff or acetylcholine during a dream. As this review will attempt to show, it is likely that acetylcholine, acting as a neurotransmitter on a muscarinic synapse within the dorsal tegmentum of the pons, triggered the dream that resulted in its own discovery.Evidence for the involvement of acetylcholine with Rapid Eye Movement (REM) sleep comes both from human and animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
1
10
0
2
Order By: Relevance
“…We confirmed these findings in another nonoverlapping sample of 20 antipsychotic-naive and 20 drug-free previously medicated schizophrenic patients and 20 healthy controls (Maixner et al 1996). Considering known cholinergic effects on REM latency and other sleep measures Gillin and Sitaram 1984), these data are consistent with the hypothesis of increased cholinergic activity in schizophrenia and its implication in the production of negative symptoms. In related studies (Taylor et al 1991;Maixner et al 1998;Tandon 1997), we observed that polysomnographic measures partially normalized following antipsychotic treatment (with neuroleptics, clozapine, and risperidone).…”
Section: In Vivo Measurement Of Central Cholinergic Activitysupporting
confidence: 81%
See 2 more Smart Citations
“…We confirmed these findings in another nonoverlapping sample of 20 antipsychotic-naive and 20 drug-free previously medicated schizophrenic patients and 20 healthy controls (Maixner et al 1996). Considering known cholinergic effects on REM latency and other sleep measures Gillin and Sitaram 1984), these data are consistent with the hypothesis of increased cholinergic activity in schizophrenia and its implication in the production of negative symptoms. In related studies (Taylor et al 1991;Maixner et al 1998;Tandon 1997), we observed that polysomnographic measures partially normalized following antipsychotic treatment (with neuroleptics, clozapine, and risperidone).…”
Section: In Vivo Measurement Of Central Cholinergic Activitysupporting
confidence: 81%
“…Because multiple noncholinergic mechanisms influence both DST response and polysomnographic results, however, these data are suggestive at best and do not lend themselves to any definitive interpretation. In the hope of determining the cholinergic contribution to these abnormalities and providing a more refined index of central cholinergic function than simple baseline parameters, we turned our attention to studying the effects of cholinergic/anticholinergic modulation using polysomnography (Sitaram and Gillin 1980;Gillin and Sitaram 1984).…”
Section: Effects Of Biperiden On Polysomnographic Measures In Schizopmentioning
confidence: 99%
See 1 more Smart Citation
“…A neurotransmitter mechanism could also play a role in the pathophysiology of RBD as it has been proposed the ratio of cholinergic to aminergic activity facilitates REM sleep,[43] in which acetylcholine has multiple roles. [44] Though report of nightmares and enhanced dreaming with acetylcholinesterase inhibitor poisoning are available,[45] patients with RBD taking acetylcholinesterase inhibitors have been reported to have both lessened response in RBD outcomes [23] as well as improvement. [46] Melatonin inhibits calmodulin which then may modulate skeletal muscle acetylcholine receptors.…”
Section: 1 Discussionmentioning
confidence: 99%
“…However, this hypothesis was opposed by some psychiatrists. Gillin administered scopolamine to healthy volunteers for 3 days, and these volunteers developed major sleep disturbances characteristic of depression, including a shortened REM latency, but they did not develop symptoms of depression . Furthermore, in other studies, bupropion and Nefazodone did not suppress REM sleep despite being effective antidepressants.…”
Section: Discussionmentioning
confidence: 95%